2019
DOI: 10.1021/acscatal.9b01897
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Oxygen Activation/Oxidation Sites for Efficient Soot Combustion over Silver Catalysts Interacted with Nanoflower-Like Hydrotalcite-Derived CoAlO Metal Oxides

Abstract: Catalytic oxidation is an effective way to eliminate soot pollution emitted from diesel engines. However, the origination and specific location of active oxygen species are still unclear over noble metal catalysts because of the complex gas (oxygen)–solid (catalyst)–solid (reactant) reaction systems. Herein, we report the high catalytic performance of the nanoflower-like hydrotalcite-derived CoAlO-supported Ag catalyst synthesized by a facile hydrothermal method for soot combustion. Our characterization result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 58 publications
1
46
0
1
Order By: Relevance
“…As shown in Figure a, the Co 6 -Al 3 _HT catalyst presented two hydrogen consumption peaks extending from 200 to 400 °C and 450 to 870 °C, respectively. The weak peak extending from 200 to 400 °C could be attributed to the more easily reducible cobalt oxide species (CoO x ) at the surface of the catalyst, while the broad peak arising from 450 to 870 °C with a maximum at 751 °C corresponded to the further reduction of Co­(II) formed in the first reduction step and/or present in the spinel. , On the other hand, TPR profiles of Co 6‑x -Ca x -Al 3 _HT samples also showed two similar hydrogen consumption peaks extending from 200 to 400 °C and 450 to 800 °C, respectively (Figure b–f). The first reduction step was related to the reduction of more easily reducible CoO x at the surface, and the second (with a maximum at 700 °C) was attributed to the reduction of Co­(II) species.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure a, the Co 6 -Al 3 _HT catalyst presented two hydrogen consumption peaks extending from 200 to 400 °C and 450 to 870 °C, respectively. The weak peak extending from 200 to 400 °C could be attributed to the more easily reducible cobalt oxide species (CoO x ) at the surface of the catalyst, while the broad peak arising from 450 to 870 °C with a maximum at 751 °C corresponded to the further reduction of Co­(II) formed in the first reduction step and/or present in the spinel. , On the other hand, TPR profiles of Co 6‑x -Ca x -Al 3 _HT samples also showed two similar hydrogen consumption peaks extending from 200 to 400 °C and 450 to 800 °C, respectively (Figure b–f). The first reduction step was related to the reduction of more easily reducible CoO x at the surface, and the second (with a maximum at 700 °C) was attributed to the reduction of Co­(II) species.…”
Section: Resultsmentioning
confidence: 97%
“…As is well known, the higher the Ce 3+ and Co 2+ concentration in these samples, the more oxygen defects are generated ( Zhao et al., 2019 ; Liu et al., 2009 ). Therefore, the surface oxygen defects associating with the Co 2+ and Ce 3+ of the 3%Co/CeO 2 catalyst gradually disappeared, with the increase of aging temperature ( Zhao et al., 2019 ; Cui et al., 2020 ; Wang et al., 2018 ; Ren et al., 2019 ). Figure S10 showed that the O 1s spectra of all catalysts can be deconvoluted into two kinds of O species, with the peak at higher binding energy being attributed to the surface oxygen species (O α ) and the peak at lower binding energy being ascribed to the lattice oxygen species (O β ) ( Xu et al., 2020 ; Ren et al., 2019 ; Sellers-Anton et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, post-treatment technology is considered to be one of the effective ways to eliminate soot particles. However, since the spontaneous combustion temperature of soot particles (550-650 • C) is higher than the exhaust temperature of the diesel engine (150-450 • C), the development of new catalysts with low cost and excellent catalytic performance is one of the main challenges in the application of post-treatment technology [5,6].…”
Section: Introductionmentioning
confidence: 99%